Employment restructuring and the labor market status of young black men in the 1980s - David R. Howell (Levy Economics Institute of Bard College, 1991)
This paper examines the effects of recent employment restructuring on young workers by race and sex. Detailed Census occupations are grouped into 10 job segments based on earnings, education and annual hours worked in 1979. Job segments in which young black men were most concentrated had the lowest employment and earnings growth but the highest growth in educational requirements (job cost) over the 1979-89 decade. The results were similar but not as severe for young white men. White women appear to have benefitted most from these trends. While the distributions of moderately educated young black and white women among segments converged over the course of this decade, the black and white male distributions diverged sharply: for those with similar educational attainment, the redistribution of young black men among job segments left them even more disadvantaged than they were in 1979. Changes in labor market participation rates for young workers in these four race/sex groups are consistent with these demand-side developments, declining most for young black males and increasing most for young white women.
Keywords: 330